2020
DOI: 10.1002/jnr.24626
|View full text |Cite
|
Sign up to set email alerts
|

Mu opioid receptor in microglia contributes to morphine analgesic tolerance, hyperalgesia, and withdrawal in mice

Abstract: A major challenge in medicine is developing potent pain therapies without the adverse effects of opiates. Neuroinflammation and in particular microglial activation have been shown to contribute to these effects. However, the implication of the microglial mu opioid receptor (MOR) is not known. We developed a novel conditional knockout (cKO) mouse line, wherein MOR is deleted in microglia. Morphine analgesic tolerance was delayed in both sexes in cKO mice in the hot plate assay. Opioid-induced hyperalgesia (OIH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 89 publications
1
33
1
Order By: Relevance
“…Consistent with these results, multiple studies have shown that morphine does not induce microglial proinflammatory cytokines in vitro (El-Hage et al 2006;Turchan-Cholewo et al 2009), and morphine alone has no effect on NF-kB, a precursor to microglial activation and production of proinflammatory cytokines (Gessi et al 2016), suggesting that specifically hippocampal microglia may not play a major role in opiate dependence and withdrawal. However, there is extensive literature on the interaction between microglia and opioid dependence and withdrawal that shows microglia, particularly in the spinal cord, is involved in regulating multiple cytokines and drugseeking behaviors (Bland et al 2009;Grace et al 2016;Hutchinson et al 2009;Reiss et al 2020). It would be interesting to determine whether chronic escalating heroin administration can be employed to study heroin withdrawal-induced changes in microglia in the spinal cord both across heroin administration and during withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these results, multiple studies have shown that morphine does not induce microglial proinflammatory cytokines in vitro (El-Hage et al 2006;Turchan-Cholewo et al 2009), and morphine alone has no effect on NF-kB, a precursor to microglial activation and production of proinflammatory cytokines (Gessi et al 2016), suggesting that specifically hippocampal microglia may not play a major role in opiate dependence and withdrawal. However, there is extensive literature on the interaction between microglia and opioid dependence and withdrawal that shows microglia, particularly in the spinal cord, is involved in regulating multiple cytokines and drugseeking behaviors (Bland et al 2009;Grace et al 2016;Hutchinson et al 2009;Reiss et al 2020). It would be interesting to determine whether chronic escalating heroin administration can be employed to study heroin withdrawal-induced changes in microglia in the spinal cord both across heroin administration and during withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that astrocytic DOR contributes to DOR-mediated tolerance in females. Recently, we have shown that MOR deletion in microglia delayed analgesic tolerance to morphine, indicating a role for microglial MOR in this morphine chronic effect (Reiss et al, 2020 ). Also, astrocytic MOR activity was shown to be involved in MOR-dependent long-term potentiation in the hippocampus and in morphine-induced conditioned place preference, although tolerance was not studied (Nam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 93%
“…The numbers of males and females of each genotype from each brain area were as follows: dorsal root ganglia, DOR-flox, n = 4 males, n = 6 females; GFAP-DOR-KO, n = 5 males, n = 7 females; spinal cord, DOR-flox, n = 5 males, n = 5 females; GFAP-DOR-KO, n = 5 males, n = 8 females; olfactory bulb, DOR-flox, n = 4 males, n = 6 females; GFAP-DOR-KO, n = 5 males, n = 7 females; cortex, DOR-flox, n = 6 males, n = 9 females; GFAP-DOR-KO, n = 4 males, n = 5 females; hippocampus, DOR-flox, n = 6 males, n = 7 females; GFAP-DOR-KO, n = 4 males, n = 6 females; caudate putamen, DOR-flox, n = 6 males, n = 6 females; GFAP-DOR-KO, n = 4 males, n = 3 females; periacqueductal gray, DOR-flox, n = 12 males, n = 5 females; GFAP-DOR-KO, n = 9 males, n = 4 females; brainstem, DOR-flox, n = 6 males, n = 8 females; GFAP-DOR-KO, n = 7 males, n = 6 females. Quantitative RT-PCR was performed on tissues and isolated astrocyte RNA as described (Reiss et al, 2020 ). Briefly, total RNA was extracted with a Nucleospin kit (Macherey Nagel, Hoerdt, France) and precipitated overnight with acetate/ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is critical to use complementary strategies of microglial manipulations. CD11b-Cre-driven CKO of BDNF and Cx3cr1-Cre-driven CKO of MOR were reported to impair thermal OIH [17; 33]. However, because CD11b and Cx3cr1 are also expressed in multiple other cell types in addition to microglia [24; 27; 31], the possibility that the CKOs in non-microglial cells caused the observed impairment of thermal OIH in mutant mice has not been conclusively excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Selective inhibition by minocycline or by anti-MAC1 (CD11B)-saporin impaired the expression of thermal hyperalgesia induced by morphine[17; 20]. Conditional knockout (CKO) of BDNF induced by CD11b-Cre and CKO of Mu opioid receptor (MOR) driven by Cx3cr1-Cre were reported to impair thermal OIH[17; 33]. It was also reported that opioids simulated microglia via Toll-like receptor 4 (TLR4) [21], and activated microglia may promote OIH expression by releasing signaling molecules such as cytokines, BDNF and ATP[35].…”
Section: Introductionmentioning
confidence: 99%